Percutaneous closure of iatrogenic anterior mitral leaflet perforation: a case report - Naeim, Hesham Abdo (Eur Heart J Case Rep, 2020)
BACKGROUND: Severe mitral regurgitation (MR) through the body of the anterior mitral leaflet (AML) is rare. The cause either iatrogenic during open-heart surgery or due to infective endocarditis. We present a case where a successful percutaneous closure of the AML perforation was an alternative to surgery. CASE SUMMARY: A 60-year-old male presented with shortness of breath (SOB) class III of 12 months duration. He underwent coronary artery bypass surgery with four grafts plus mitral valve (MV) repair 20 months ago. Transthoracic echocardiogram (TTE) and transoesophageal echocardiogram (TOE) revealed severe MR through the body of AML at A3. The percutaneous closure plan was to cross the AML perforation from the left ventricular side. The venacontracta of the perforation was 6 mm, an amplatzer septal occluder device 6 mm considered appropriate for closure of this hole. A snare catheter snared the wire and exteriorized creating arteriovenous loop. Amplatzer septal occluder 6 mm loaded to the delivery system till larger disc (left-sided) opened safely and freely below the MV apparatus. Once the left ventricular side disc opposed the ventricular surface of AML, the waist and left atrial disc gently released. The patient discharged in the next day. After 6 months, the patient had no more SOB, he returned to his daily activity. Follow-up TTE showed no MR, the closure device was stable in place. DISCUSSION: We added a successful case of transcatheter AML perforation to the literature. The role of TOE is crucial in diagnosis and procedure guidance.